The Role of Tax Sanctions in Improving Taxpayer Compliance: A Literature Review - Safda, Ulfiyah Zakiyah; Wawo, Andi Basru; Tamburaka, Sulvariany (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Although reaching governmental income goals depends heavily on taxpayer compliance, Indonesia's official compliance rate is still below ideal. Using a literature review methodology, this study sought to examine how tax penalties might enhance taxpayer compliance. Using a literature review, the research approach examined 12 earlier papers from 2020–2024 that were found using Google Scholar.  The findings indicated that while 16.7% of studies revealed insignificant effects, the majority of studies (83.3%) found that tax sanctions have a favorable and significant influence on taxpayer compliance.  Tax penalties consistently work for many types of taxpayers, including individuals, corporations, and MSMEs. According to the study's findings, tax penalties significantly increase taxpayer compliance in Indonesia, demonstrating the applicability of deterrence theory in the country's tax system. However, other elements including regulatory knowledge, the caliber of tax authority services, and favorable economic conditions must be present in order for tax punishments to be effective.